Lifestyle and Food Habits Impact on Chronic Diseases: Roles of PPARs - d’Angelo, Michele (Int J Mol Sci, 2019)
Peroxisome proliferator-activated receptors (PPARs) are nuclear receptors that exert important functions in mediating the pleiotropic effects of diverse exogenous factors such as physical exercise and food components. Particularly, PPARs act as transcription factors that control the expression of genes implicated in lipid and glucose metabolism, and cellular proliferation and differentiation. In this review, we aim to summarize the recent advancements reported on the effects of lifestyle and food habits on PPAR transcriptional activity in chronic disease.